Analyzing the concept of fluid overload in Chronic Kidney Disease patients in dialysis therapy: an integrative review - Maria Isabel da Conceição Dias Fernandes; Bertha Cruz Enders; Ana Luisa Brandão de Carvalho Lira (SciELO, 2018)
ABSTRACT Objective To analyze the concept of fluid overload in Chronic Kidney Disease patients undergoing dialysis therapy and comparing it to the Nursing Diagnosis of Excess fluid volume present in the NANDA International. Method An integrative literature review carried out in the LILACS, CINAHL and SCOPUS databases. Results The sample was comprised of 22 articles. The defining attributes of the concept were: fluid retention, fluid buildup in the body, and weight gain over a short period; while the attributes composing the definition were: fluid retention in the body (intracellular/extracellular space) expressed by weight gain over short period of time. Twenty-one (21) antecedents and 22 consequents of fluid overload in patients with renal disease in dialysis therapy were identified. Conclusion The definition evidenced by the NANDA International taxonomy for the Excess fluid volume Nursing Diagnosis and the components of this diagnosis need to be complemented in order to better target the care of patients with kidney disease undergoing dialysis therapy.